Nephrogenic diabetes insipidus, cystinosis, and vitamin D. Issue 5 (May 1988) - Katzir, Z; Shvil, Y; Landau, H; Kidrony, G; Popovtzer, M M
Abstract : We describe a patient with early diagnosed cystinosis who presented with nephrogenic diabetes insipidus in addition to proximal tubular dysfunction. Another feature in this patient was abnormally low serum concentration of 24, 25 dihydroxy vitamin D3 (24, 25(OH)2D3) with normal 25 hydroxy vitamin D3 (25(OH)D3) and relatively low 1, 25 dihydroxy vitamin D3 (1, 25(OH)2D3).